A Case Report on Gingivectomy, For the Management Of Orthodontic Treatment Induced Gingival Enlargement - Pooja Bharadwaj; Anushri Gupta; N Sai Sri Harsha; Nida Malik (Journal of Orofacial Research, 2021)
Gingival enlargement initially known as gingival hyperplasia, is the most common feature of many conditions such asinflammation, drug induced, and systemic conditions such as pregnancy, diseases such as leukemia, treatment induced such asorthodontic treatment induced gingival enlargement. This orthodontic treatment induced gingival enlargement is due to thepresence of nickel ions in the orthodontic bands, which result in fibroblastic proliferation. As a result of this enlargement, thereis an inability to maintain proper oral hygiene. Gingivectomy is the treatment of choice for this type of gingival enlargement asit helps in the reduction or elimination of pseudopockets, suprabony pockets, which is common in orthodontic induced gingivalenlargement. Present case report is on a 21years old female patient who was undergoing orthodontic treatment, and reported tothe department of Periodontology for the orthodontic treatment induced gingival enlargement. Gingivectomy was performed forthis patient and after one week follow up, the patient shows positive changes as there was no suprabony pocket present.